2018
DOI: 10.1002/ehf2.12334
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide and weight loss among patients with advanced heart failure and a reduced ejection fraction: insights from the FIGHT trial

Abstract: Liraglutide is an efficacious weight loss agent in patients with HFrEF. These findings will require further exploration in a well-powered cardiovascular outcomes trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…At baseline, the median trial mean glycated haemoglobin A1c was 8.1% and BMI was 30.1. Eligibility criteria included coronary artery disease or macrovascular disease in 35 trials, 3 6 7 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 atrial fibrillation in 1 trial, 65 heart failure in 9 trials, 66 67 68 69 70 71 72 73 74 chronic kidney disease and/or albuminuria in 37 trials, 8 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 …”
Section: Resultsmentioning
confidence: 99%
“…At baseline, the median trial mean glycated haemoglobin A1c was 8.1% and BMI was 30.1. Eligibility criteria included coronary artery disease or macrovascular disease in 35 trials, 3 6 7 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 atrial fibrillation in 1 trial, 65 heart failure in 9 trials, 66 67 68 69 70 71 72 73 74 chronic kidney disease and/or albuminuria in 37 trials, 8 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 …”
Section: Resultsmentioning
confidence: 99%
“…With regard to effects on HF, the CVOTs did not find that GLP‐1RAs reduced hospitalizations for HF (Table ), even though early small studies on exenatide showed HF benefits in the immediate post‐MI period. With liraglutide, in some small studies, there appeared to be worse outcomes in patients with T2DM who had severe congestive heart failure; however in the large LEADER study there was no adverse effect on HF outcomes …”
Section: Ascvd Vs Hf Benefits In the Cvotsmentioning
confidence: 99%
“…With liraglutide, in some small studies, there appeared to be worse outcomes in patients with T2DM who had severe congestive heart failure; however in the large LEADER study there was no adverse effect on HF outcomes. 30,36,37…”
Section: Dpp-4 Inhibitor Cvotsmentioning
confidence: 99%
“…The preliminary results of FIGHT trial, that evaluates weight reduction benefit in patients with heart failure, showed that liraglutide was associated with a significant weight reduction and decreased triglyceride levels. However, the cardioprotective effects on patients with reduced left ventricular ejection fraction were not significant (32,33).…”
Section: Evidence Of Glp-1 Agonists On Metabolismmentioning
confidence: 99%